PEMBERDAYAAN SD KUMALA BAYANGKARI MAKASSAR MELALUI EDUKASI DAN AKSI PEMBUATAN PUPUK KOMPOS TAKAKURA - Puspitasari, Dewi; Ramli, Hartini; Hidayat, Akmal; Muis, Abdul; Ristiana, Evi; Aswar (Jurnal Pengabdian Kepada Masyarakat Patikala, 2023)
AbstractIn Law no. 18 of 2008 Article 12 states that waste management must be environmentally sound so that awareness and real action from the community are highly expected in supporting this policy. To realize this, it is necessary to hold organic waste management training activities so that the community is moved and aware of the importance of their participation in waste management, especially within the school sphere. Based on observations made at Kemala Bhayangkari Elementary School it was found that the awareness of school residents in waste management, especially organic waste, is still very low. Therefore, the service team compiled an agenda for the implementation of the Takakura Compost Fertilizer Training, namely making Takakura compost, in order to create independent and productive school residents through Organic Waste Management. Making Takakura compost is relatively practical and simple, because it doesn't require land, so it's very suitable for small scale. This activity can also support the school to remain beautiful and clean and avoid air pollution, which causes bad odors. The results of processing organic waste into Takakura compost can also be used as a good planting medium to help schools plant green trees so that schools remain beautiful. The implementation of this training started with a field survey and coordination with the school, followed by program socialization and program implementation. In the implementation process, starting from the stages: 1) Garbage collection, 2) Waste segregation, 3) Implementation preparation, in the form of preparation of supporting tools and materials, 3) Takakura composting, and 4) Trial. Lastly is the evaluation of activities that aim to evaluate the progress of the implementation of takakura composting at Kemala Bhayangkari Elementary School. The results of the training show that with the new skills they already have, the participants' awareness of organic waste management is also increasing.